Preparation and Characterization of (Au/n-SnO2/SiO2/Si/Al) MIS Device for Optoelectronic Application - Marwa Abdul Muhsien; Evan T. Salem; Ibrahim R. Agool (International Journal of Optics)
SnO2 thin films were prepared by using rapid thermal oxidation (RTO) of Sn at oxidation temperature 873 K and oxidation time 90 sec on semiconductor n-type and p-type silicon substrate. In order to characterize the prepared device, the electrical properties have been measured which revealed that the barrier height is greatly depended on interfacial layer thickness (SiO2). The value of peak response (n-SnO2/SiO2/n-Si) device was 0.16 A/W which is greater than that of (n-SnO2/SiO2/p-Si) device whose value was 0.12 A/W, while the rise time was found to be shorter.